1997
DOI: 10.1136/jech.51.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the 12 months after discharge from psychiatric inpatient care, Scotland 1968-92.

Abstract: Study objective-To investigate the rate of suicide in the 12 months after discharge from psychiatric hospital and to determine its relationship to age, diagnosis, and period. Design-Cohort study of patients discharged from psychiatric hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 8 publications
2
40
0
1
Order By: Relevance
“…Two cohort studies also reported higher suicide rates in depressed patients immediately after hospital discharge (24,25). A third study did not find an association (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two cohort studies also reported higher suicide rates in depressed patients immediately after hospital discharge (24,25). A third study did not find an association (26).…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressant treatment in the follow-up period was largely inadequate, and patients with a prior suicide attempt did not receive more vigorous care than nonattempters. For each suicide attempt in the subject's history, the risk for an attempt in the follow-up period increased by 30%.Two cohort studies also reported higher suicide rates in depressed patients immediately after hospital discharge (24,25). A third study did not find an association (26).…”
mentioning
confidence: 99%
“…Suicide is the third leading cause of death for adolescents and young adults, and the 10th leading cause for all ages. Multiple studies have determined that patients are at increased risk for suicide after a recent discharge from an inpatient psychiatric unit, particularly in the immediate postdischarge period (Dougal et al, 2014;Geddes, Juszczak, O'Brien, & Kendrick, 1997;Goldacre, Seagroatt, & Hawton, 1993;Ho, 2003;Isometsa, Henriksson, Heikkinen, & Lonngvist, 1993;Meehan et al, 2006;Qin & Nordentoft, 2005). Qin and Nordentoft (2005) found that patients were at highest risk for suicide in the first week after discharge.…”
mentioning
confidence: 99%
“…The risk of suicide is greatest in the year after discharge from hospital, of the order of 48 to 61 per 10 000 patient years (Fawcett et al, 1990;Geddes et al 1997;Rossau & Mortensen, 1997). In a recent US study, the risk of violence in the year following hospital discharge was 1990/10 000 (19.9%) for patients with mental illness without substance misuse problems, and 3110/10 000 for those with mental illness and comorbid substance misuse (Steadman et al, 1998).…”
Section: Risk Is Stratified In Timementioning
confidence: 99%
“…Others have made the same case for the impossibility of predicting suicide (Geddes, 1999). Based on a 12-month prevalence of psychosis of 4 in 1000 (or 200 000 cases in England and Wales) and a homicide rate by people with schizophrenia (or severe mental illness) of approximately 20 per year in England and Wales (Taylor & Gunn, 1999), Szmuckler arrives at a homicide rate of 1 per 10 000 psychosis years'.…”
mentioning
confidence: 99%